Self-Regulated Learning Strategies Among Graduate Students and Their Relationship with Statistics Anxiety - Nasser H. Youssef; Essa A. Alibraheim (Education Sciences)
The research set out to investigate Saudi Arabian graduate students’ levels of anxiety related to statistics and their use of self-regulated learning strategies. Research tools were created, such as a measure for measuring statistics anxiety and a measure for measuring the usage of self-regulated learning strategies, in order to meet the research objectives. Sixty-six master’s students from Imam Abdulrahman Bin Faisal University’s College of Education received these instruments. The findings showed that participants’ levels of anxiety related to statistics were moderate, and their use of self-regulated learning strategies was quite high. The results additionally demonstrated an inverse correlation between graduate students’ use of self-regulated learning strategies and statistics anxiety. Regression analysis revealed that self-regulated learning strategies significantly predicted levels of statistics anxiety. This suggests that enhancing self-regulated learning strategies could potentially mitigate statistics anxiety among graduate students. The research recommends the development of a comprehensive guide for self-regulated learning strategies for master’s students, including multiple examples for each strategy, the creation of training programs to enhance self-regulated learning strategies, and raising awareness about statistics anxiety among graduate students.